Expertise, politics and public opinion at the crossroads of the European Commission’s decision-making: The case of Glyphosate. - Giulia Bazzan; Marta Migliorati (International Review of Public Policy)
With the growing politicisation of European Union (EU) integration, the European Commission is increasingly facing a tension between technocratic and responsive decision-making. How does this tension play out in the process of supranational implementation under comitology rules? We argue that the tension between the Commission´s role as a technocrat and as a responsive bureaucrat takes place during the implementation process when the issue at stake becomes politicised. We test our argument through the analysis of the Glyphosate renewal procedure (2015-2017). We process-trace the case by means of semi-structured interviews, media and document analysis. We find that with the increase of issue visibility and subsequent politicisation, the Commission progressively abandons a purely technocratic behaviour. First, it puts in place political strategies such as delays and blame-shifting to release itself from the burden of unpopular decisions. Secondly, it seeks to respond to concerns expressed by consumers by proposing compromise-based measures closer to public interest. Ultimately, we show how the outcome of the policy process is mediated by politicisation and characterised by a shift from technocratic to responsive decision making.